Hepatitis B e antigen induces the expansion of monocytic myeloid-derived suppressor cells to dampen T-cell function in chronic hepatitis B virus infection - Yang, Feifei; Yu, Xueping; Zhou, Chenliang; Mao, Richeng; Zhu, Mengqi; Zhu, Haoxiang; Ma, Zhenxuan; Mitra, Bidisha; Zhao, Gan; Huang, Yuxian; Guo, Haitao; Wang, Bin; et al. (PLoS pathogens, 2019)
Chronic hepatitis B virus (HBV) infection is associated with functionally impaired virus-specific T cell responses. Although the myeloid-derived suppressor cells (MDSCs) are known to play a critical role in impairing antiviral T cell responses, viral factors responsible for the expansion of MDSCs in chronic hepatitis B (CHB) remain obscure. In order to elucidate the mechanism of monocytic MDSCs (mMDSCs) expansion and T cell function suppression during persistent HBV infection, we analyzed the circulation frequency of mMDSCs in 164 CHB patients and 70 healthy donors, and found that the proportion of mMDSCs in HBeAg (+) CHB patients was significantly increased compared to that in HBeAg (-) patients, which positively correlated with the level of HBeAg. Furthermore, exposure of peripheral blood mononuclear cells (PBMCs) isolated from healthy donors to HBeAg led to mMDSCs expansion and significant upregulation of IL-1β, IL-6 and indoleamine-2, 3-dioxygenase (IDO), and depletion of the cytokines abrogated HBeAg-induced mMDSCs expansion. Moreover, HBeAg-induced mMDSCs suppressed the autologous T-cell proliferation in vitro, and the purified mMDSCs from HBeAg (+) subjects markedly reduced the proliferation of CD4+ and CD8+ T cells and IFN-γ production, which could be efficiently restored by inhibiting IDO. In summary, HBeAg-induced mMDSCs expansion impairs T cell function through IDO pathway and favors the establishment of a persistent HBV infection, suggesting a mechanism behind the development of HBeAg-induced immune tolerance.